An investigation of the impact of pump deformations on circumferential gap height as a factor influencing volumetric efficiency of external gear pumps - Cieślicki, Rafał; Karpenko, Mykola (Transport, 2022)
Gear pumps are widely used in transport machines not only in hydraulic drive systems, but also in lubrication and fuel systems. A positive displacement pump converts mechanical energy into pressure energy stored in the liquid, which it transports to the hydraulic cylinder or motor. The efficiency of this process depends on the efficiency of the system components, including the efficiency of the pump, which depends on the amount of internal leakage through the gaps between the high and low pressure sides. The larger the gaps, the lower the volumetric efficiency. This article presents an investigations of impact of pump deformations on circumferential gap height. The article presents a three-dimensional model of an external gear pump using Finite Element Method (FEM) during operating conditions. The model reflects pumping operation at discharge pressures up to 32 MPa and it was validated against strain measurements of pump casing. The simulation results indicate that the pump casing becomes deformed due to pressure, causing a significant increase in the height of the circumferential gap. The increase of the discharge pressure from 8 to 32 MPa causes more than twofold local increase in the height of the circumferential gap. The obtained results indicate that for the correct modelling of the flow generated by gear pumps, it is necessary to consider the change in the size of the gaps resulting from the deformation of the pump.